Characteristics, treatment patterns, healthcare resource use, and costs among pediatric patients diagnosed with neurofibromatosis type 1 and plexiform neurofibromas: a retrospective database analysis of a medicaid population. (2nd September 2021) - Yang, Xiaoqin; Desai, Kaushal; Agrawal, Neha; Mirchandani, Kirti; Chatterjee, Sagnik; Sarpong, Eric; Sen, Shuvayu
Abstract: Objectives: The objectives of this study were to describe the characteristics and initial treatment patterns, healthcare resource use (HCRU), and costs of patients newly diagnosed with neurofibromatosis type 1 (NF1)-related plexiform neurofibromas (PN). Methods: This was a retrospective study of individuals enrolled in the IBM MarketScan Multi-State Medicaid database from 1 October 2014 to 31 December 2017. Patients aged ≤18 years at the index date (first diagnosis of NF1 or PN, whichever occurred later) with at least 1 ICD-10-CM diagnosis code for both NF1 and PN were included. All-cause HCRU and the associated direct costs during the follow-up period were calculated per patient per year (PPPY) in 2018 USD. Results: A total of 383 patients were included with a mean follow-up of 448 days. Most patients were diagnosed by a specialist (63.5%). During the follow-up period, pain medications were used by 58.5% of patients, 25.1% were treated with chemotherapy, 7.1% received surgery for PN, 1.6% received MEK inhibitors, and 0.8% received radiation. Mean PPPY inpatient, outpatient, ER, pharmacy, and other visits were 1.4, 17.3, 1.6, 13.6, and 25.8, respectively. Mean ± SD (median) total PPPY healthcare costs were $17, 275 ± $61, 903 ($2889), with total medical costs of $14, 628 ± $56, 203 ($2334) and pharmacy costs of $2646 ± $13, 303 ($26). Conclusions: This study showed that many pediatric patients newly diagnosed with NF1 and PN were initially treated with supportive care only, highlighting a substantial unmet medical need. This study also highlights the considerable economic burden among patients with NF1 and PN.